Hormone replacement therapy: does the dose matter? - Jakiel, Grzegorz; Słabuszewska-Jóźwiak, Aneta; Baran, Arkadiusz; Bińkowska, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2013)
The aim of hormone replacement therapy is to treat vasomotor symptoms with the lowest dose. The choice of the dose, route of administration and time of initiation of therapy should be adapted to the individual needs of women, and should account for the potential side effects of treatment.